HIV/AIDS: A Case-Based Learning Module for First-Year Medical Students - Timothy J. Bauler; Shanna Cole; Tyler Gibb; Richard Van Enk; Larry Lutwick; Bonny L. Dickinson (Journal of Microbiology & Biology Education, 2018)
In medical and healthcare-related education, case-based learning (CBL) is a teaching strategy that uses clinical cases to engage students in active learning using course concepts to solve important problems. Here we describe the design and implementation of a CBL module to teach first year medical students about the human immunodeficiency virus (HIV), acute retroviral syndrome, clinical progression to acquired immunodeficiency syndrome, HIV diagnostics, assays used to assess stage of disease and response to antiretroviral treatment, and highly active antiretroviral therapy. A team of basic science and clinical faculty in the disciplines of microbiology, immunology, infection prevention and control, clinical medicine, pharmacology, and medical ethics collaboratively designed the CBL module. The results of a questionnaire indicated that the students found the CBL case interesting, engaging, and a useful educational strategy for linking basic science concepts to important clinical problems. In our experience, the CBL promoted student synthesis of basic science concepts across disciplines and engaged learners in the application of basic science knowledge to address significant real-world clinical problems.